A Creative Use of Films to Enhance Emotional Awareness and Cultural Intelligence - Yang, Chulguen Charlie; Nodoushani, Omid (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Domain specificity of sex differences in competition - Wieland, Alice; Sarin, Rakesh (Journal of Economic Behavior & Organization, 2012)
There has been much recent literature about sex differences in competition, mostly noting that women are innately less competitive than men (Croson and Gneezy, 2009). This article examines the hypothesis that sex differences in propensity to compete are domain specific. We conducted a 2 (sex)×4 (domain) experiment with 434 participants examining competition decisions, familiarity with the domain, and performance. We find no overall sex differences in rates of competition when collapsing across all four domains, but do find sex differences in rates of competition for individual domains. Additionally we examined the importance of winning at competition on self-esteem using the Contingencies of Self-Worth, Competition subscale (Crocker et al., 2003) and find that the subscale fully mediates the effect of sex on the strength of competitive pay preferences.
Keywords: Competition; Decision-making; Gender differences; Risk; Sex differences; dept.mgt

Sustainability and Embodiment: How Can You Be in Two Places at Once When You’re No Place at All? - Robbins, Gregory (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Sustainability initiatives: a competing values framework - Robbins, Gregory E.; Page, Mary A. (Competition Forum, 2012)
Keywords: dept.mgt; peer-reviewed

Telling tales at work: an evolutionary psychological explanation - Yang, Chulguen (Academy of Management Proceedings, 2012)
Keywords: dept.mgt